IMMIGRANT WORKERS IN BRAZIL: Obstacles to Accessing Justice and Legal Protection Alternatives (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This article analyzes the contemporary migration reality in Brazil, where immigrants from the Global South, driven by the search for dignity and survival, frequently face exploitation and invisibility, especially in the informal labor market. Barriers such as lack of documents, language difficulties, unawareness of rights, xenophobia, and racism often lead many to conditions analogous to slavery. Despite a robust legal framework, including the 1988 Federal Constitution and the 2017 Migration Law, guaranteeing equal rights between Brazilians and foreigners, a significant gap persists between the norm and practice. Access to justice for these workers is complex due to bureaucracy, misinformation, and normative omissions, even with favorable labor jurisprudence. The article proposes improving access to information and legal assistance, strengthening oversight, and consolidating a State migration policy that fully recognizes migrants' rights.